Estimation of Ground Profiles Based on Microtremor Survey in the Bangkok Basin - Subedi, Bidhya; Kiyono, Junji; Furukawa, Aiko; Ono, Yusuke; Ornthammarath, Teraphan; Kitaoka, Takafumi; Charatpangoon, Bhuddarak; Latcharote, Panon (Frontiers in Built Environment, 2021)
Multiple earthquakes have been felt in high-rise buildings in Bangkok despite the epicenters being far away. Seismic wave recordings in the Bangkok basin show a low-frequency peak. This study uses horizontal-to-vertical spectral ratio (HVSR) analysis and array analysis of ambient vibration data to find the predominant period of the ground and the shear wave velocity profiles at five sites in Bangkok. The accuracy of the accelerometer used for the ambient data recording was verified by comparing results with velocity-meter results. The estimated predominant period was within 0.68–0.86 s. From the array records, dispersion curves of the Rayleigh-wave phase velocity were extracted and inverted for the deep layers. The results show that the shear-wave velocity of the top clay layer is low (82–120 m/s) at depths of 11–14.3 m. The low-frequency peak in the HVSR of the earthquake data, and the sediment layer with low shear-wave velocity implies that Bangkok is at risk of amplification of long-period earthquake waves.